2023
DOI: 10.1111/jre.13171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of periodontal cells‐derived extracellular vesicles on mesenchymal stromal cell function

Pingping Han,
Nigel Johnson,
Abdalla Abdal‐hay
et al.

Abstract: ObjectiveTo enrich and compare three extracellular vesicles—EV subtypes (apoptotic bodies, microvesicles and small EV) from three periodontal cells (periodontal ligament cells—PDLCs, alveolar bone‐derived osteoblasts—OBs and gingival fibroblasts—GFs), and assess uptake and cell function changes in buccal fat pad‐derived mesenchymal stromal cells (BFP‐MSCs).BackgroundPeriodontal cells such as PDLCs, OBs and GFs have the potential to enhance bone and periodontal regeneration, but face significant challenges, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…It was found that when the exosomes were cultured with osteogenic differentiation media, osteoblastic differentiation markers, including OCN, OPN and RUNX2, were all upregulated 61 . The study by Han et al 81 . investigated 3 sources of exosomes on buccal fat pad‐derived mesenchymal stromal cells (BFP‐MSCs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that when the exosomes were cultured with osteogenic differentiation media, osteoblastic differentiation markers, including OCN, OPN and RUNX2, were all upregulated 61 . The study by Han et al 81 . investigated 3 sources of exosomes on buccal fat pad‐derived mesenchymal stromal cells (BFP‐MSCs).…”
Section: Resultsmentioning
confidence: 99%
“…investigated 3 sources of exosomes on buccal fat pad‐derived mesenchymal stromal cells (BFP‐MSCs). It was concluded that hOBs‐sEVs showed superior levels of osteogenesis markers compared to hPDLCs‐sEVs and hGFs‐sEVs, while hOBs‐16 k EVs promoted adipogenic gene expression compared to hPDLCs and hGFs 81 . In summary, the interest in these studies was characterized by the study by Han et al., demonstrating that various exosomal subsets derived from multiple sources have the ability to impact various cell types differently 81 …”
Section: Resultsmentioning
confidence: 99%
“…Biodegradable materials, such as polyglycolic acid polymers, calcium phosphates ceramics, and certain biodegradable metals, undergo dissolution upon exposure to bodily fluids. Bioinert materials, like titanium, demonstrate stability within the human body and can, under specific circumstances, form both structural and functional connections with adjacent bone (Table 2) [44,46,47]. In tissue engineering, scaffolds play a vital role by maintaining space, storing growth factors, and aiding cell attachment and proliferation when applied to bone defects.…”
Section: In Situ Tissue Engineering Biomaterialsmentioning
confidence: 99%
“…GFs such as PDGFs, BMPs, IGFs, TGF-β, and VEGFs exhibit considerable potential in bone healing by modulating various cellular behaviors, including recruitment, migration, adhesion, proliferation, and differentiation. A combination of angiogenic factors (VEGF), cell recruiting factors (PDGF), and osteogenic factors (BMPs) has been devised and demonstrated to exert a synergistic effect, proving more advantages for bone repair compared with the administration of any single GF in isolation [45][46][47]. The implementation of growth factors (GFs) via scaffoldbased approaches aims to orchestrate cellular reactions by bridging the communication between cell signaling and the dynamics of bone injury recovery.…”
Section: Scaffold In Combination With Growth Factorsmentioning
confidence: 99%
“…Regenerative medicine commonly employs stem cells, particularly mesenchymal stem cells (MSCs), which possess unique faculties, like self-renewal, clonality, and potency. These adult stem cells exhibit anti-inflammatory properties and contribute to tissue repair processes, secreting mediators with various beneficial effects [28,29]. The expression of specific surface antigens, including CD44, CD73, CD90, and CD105, helps characterize MSCs, while lacking hematopoietic and endothelial markers [30].…”
Section: Introductionmentioning
confidence: 99%